Monetary and Exchange System Reforms in China : An Experiment in Gradualism - Quintyn, Marc (Occasional Papers; Occasional Paper ;, 1996)
In 1978, China embarked on a gradual but far-reaching reform of its economic system. This paper focuses on the achievements so far in reforming the financial sector, the legal framework for financial transactions, the payments system, and the monetary policy and foreign exchange system. It also analyzes the tasks ahead to achieve the goals set in these areas for the year 2000.